A crisis of rape in Bangladesh: opportunities for faith engagement - Centre for Peace and Justice (CPJ), Brac University (Brac University, 2022)
Widespread sexual violence is a persistent problem in Bangladesh, aggravated during the COVID-19 pandemic. This brief focuses on the ongoing rape crisis, examining pathways to policy reform. Its underlying premise is that faith actors can potentially be a galvanizing, positive force that influences public policy and stimulates social change.